2008
DOI: 10.1007/s10649-008-9155-z
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and use of shortcut strategies by traditionally schooled children

Abstract: This study aimed at analysing traditionally taught children's acquisition and use of shortcut strategies in the number domain 20-100. One-hundred-ninety-five second, third, and fourth graders of different mathematical achievement levels participated in the study. They were administered two tasks, both consisting of a series of two-digit additions and subtractions that maximally elicit the use of the compensation 45 þ 29 ¼ ; 45 þ 30 À 1 ¼ 75 À 1 ¼ 74 ð Þ and indirect addition strategy (71 À 68 ¼ ; 68 þ 2 ¼ 70; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 28 publications
4
61
3
5
Order By: Relevance
“…First of all, student characteristics, such as their general mathematical ability, age, and grade level (see Torbeyns et al, 2009b), are found to be of influence. Furthermore, teaching characteristics, for example, whether or not students have been taught a particular procedure, turned out to play a role, although not all researchers found this (see Section 1.3).…”
Section: Conditions Influencing Students' Procedures Usementioning
confidence: 99%
See 2 more Smart Citations
“…First of all, student characteristics, such as their general mathematical ability, age, and grade level (see Torbeyns et al, 2009b), are found to be of influence. Furthermore, teaching characteristics, for example, whether or not students have been taught a particular procedure, turned out to play a role, although not all researchers found this (see Section 1.3).…”
Section: Conditions Influencing Students' Procedures Usementioning
confidence: 99%
“…The student's use of materials and models is left out as well b These calculation steps are not very common to solve this problem; they are only given to explain this particular combination of procedure and strategy students are able to solve subtraction problems by applying IA. For example, a few recent intervention studies concluded that even students in regular primary education have difficulties using IA to solve subtraction problems (Torbeyns et al, 2009a;Torbeyns, De Smedt, Ghesquière, & Verschaffel, 2009b). Torbeyns et al (2009a) found that students have great difficulty picking up the IA procedure, even when they have been taught IA.…”
Section: Solving Subtraction Problems By Indirect Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…У нашој образовној пракси правила стал-ности збира и разлике се до четвртог разреда основне школе системски изучавају, и то кроз сва три вида изражавања, док се у страној лите-ратури (Carpenter et al, 1998;Fuson et al, 1997;Torbeyns et al, 2009) правила спомињу и користе као стратегија у рачунању, без експлицитног из-двајања и представљања овог правила. Правило називају стратегијом компензације.…”
Section: теоријске основеunclassified
“…Међутим, када им је страте-гија објашњена на хипотетичком задатку, знат-но већи број ученика је користио наведену стра-тегију као свој начин при рачунању. У истражи-вању које се бавило испитивањем неформалних стратегија рачунања (Torbeyns et al, 2009) по-себна пажња посвећена је стратегији компенза-ције. Аутори су истраживали да ли заиста -како је једно друго истраживање показало (Shrager & Siegler, 1998) -ученици могу спонтано да развију стратегију компензације при рачунању, иако то није било предмет систематске обраде.…”
Section: теоријске основеunclassified